Optimising shut-off value methodology for enhanced economic viability in sublevel caving: a case study of the Alemão Project - Soto, N.; Villa, D.; Campos Rosado, R. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Large-scale underground mining projects typically require substantial upfront capital investments for mine development and supporting infrastructure. However, these capital expenditures are often excluded from shut-off grade calculations used in mine design and mineral resource evaluation. As a result, the application of conventional fixed shut-off grade methodologies may lead to negative cash flows during the early stages of operation, potentially compromising project feasibility. The impact of capital costs becomes even more significant in projects with demanding minimum return requirements, where economic performance is highly sensitive to the timing of cash flow generation, even when operating and sustaining costs remain moderate. This was the case for the Alemão Project. This paper aims to discuss the shut-off grade methodology used to achieve the required rate of return. The methodology considers a variable shut-off grade for the different mine levels that prioritises extracting high grades in the first years of operation and recovering low grades later in the mine life. Along with this strategy, the production footprint size and extraction rate were optimised, aiming to maximise the project’s net present value.